2020
DOI: 10.1183/23120541.00270-2019
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute COPD exacerbations in Australia: do we follow the guidelines?

Abstract: ObjectiveWe aimed to assess adherence to the Australian national guideline (COPD-X) against audited practice, and to document the outcomes of patients hospitalised with an acute exacerbation of chronic obstructive pulmonary disease (COPD) at discharge and 28 days after.MethodsA prospective clinical audit of COPD hospital admission from five tertiary care hospitals in five states of Australia was conducted. Post-discharge follow-up was conducted via telephone to assess for readmission and health status.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Education and other interventions to enhance self-learning among physicians 12,38 Introduction of hospital guidelines 21 Implementation and education of updated guideline versions in clinical practice 30 Educate clinicians of the indications and contraindications for ICS a and encourage to prescribe according to the guidelines 36 Education of professionals involved in the care of COPD a patients may reduce the risk of complications of hypercapnia 52 Electronic care order set and prescribing at point of care [10][11][12]18,20,47,52 Informational posters 12 Training all nurses, pharmacists and allied health to share responsibility in inhaler device and technique education 49,58 Clinical bundles/pathways to standardise care particularly with pharmacological management 18,20,29,33,34,65 Targeted health professional education for each discipline 58 Interactive educational tools, specific cue cards in clinical practice and presence of hospital clinical champions 38 28/37…”
Section: Physical)mentioning
confidence: 99%
See 2 more Smart Citations
“…Education and other interventions to enhance self-learning among physicians 12,38 Introduction of hospital guidelines 21 Implementation and education of updated guideline versions in clinical practice 30 Educate clinicians of the indications and contraindications for ICS a and encourage to prescribe according to the guidelines 36 Education of professionals involved in the care of COPD a patients may reduce the risk of complications of hypercapnia 52 Electronic care order set and prescribing at point of care [10][11][12]18,20,47,52 Informational posters 12 Training all nurses, pharmacists and allied health to share responsibility in inhaler device and technique education 49,58 Clinical bundles/pathways to standardise care particularly with pharmacological management 18,20,29,33,34,65 Targeted health professional education for each discipline 58 Interactive educational tools, specific cue cards in clinical practice and presence of hospital clinical champions 38 28/37…”
Section: Physical)mentioning
confidence: 99%
“…Care gaps in the inpatient management of AECOPD a with guidelines 11,12,36 The prevalence of clinical depression in patients with COPD a varies from 18% to 80%, yet not screened regularly with AECOPD a , 59 Screening and pharmacological treatment for clinically confirmed depression not done as part of routine care 59 Staff time constraints and lack of enthusiasm by senior clinical staff 21,35 Clinicians lacking time to discuss palliative care or being fearful of taking away hope 61 Current health care models with insufficient communication and collaboration 29 Poor access, lack of Palliative care service capacity 61 Lack of human resources including specialists in pulmonary rehabilitation, infrastructure, and establishment of a wellequipped pulmonary rehabilitation unit 29 Lack of integration of multidisciplinary team of respirology and internal medicine ward physicians and allied health team members 36 Communication difficulties between doctors and nurses 65 Practical issues related to space and place for prescribing oxygen 32,38 Evidence for effectiveness of a specific pharmacological therapy for treating COPD a related depression is still limited 59…”
Section: /37mentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 15 Challenges in the acute clinical setting include a lack of a single integrated platform, supporting infrastructure, interdisciplinary staff capacity, lack of clinician training and support for under-confident clinicians to use digital devices, and a lack of critical information at point of care. 13 , 16 , 17 An electronic proforma acquires the desired capabilities if integrated with an existing electronic medical record to reduce interdisciplinary staff cognitive burden, and in the provision of consistent information through guidelines, consistent patient resources and information, integration of clinical data and decision making at point of care, one-step referrals within outpatient clinics and primary care, as well as consistent staff training. 18–20 Developing relevant ED-focussed quality indicators have been noted as important in improving care outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Underuse of PR is recognised as an international problem prompting the European Respiratory Society (ERS) and American Thoracic Society (ATS) to call for action to bridge the gap between the documented benefits of PR and implementation issues [ 13 ]. In Australia, observational data has shown that nearly half of all people with stable COPD and nearly three-quarters of those following an exacerbation of the disease who may benefit from PR are not referred to PR [ 15 , 16 ]. Healthcare professionals (e.g.…”
Section: Introductionmentioning
confidence: 99%